Legal Protection Against Geographical Indications of Registered Brands by Others Who Have No Rights - Sarmilah, Milah (Jurnal Scientia Indonesia, 2019)
Geographical Indication is one form of Intellectual Property Rights that must be protected. In the Trademark Law, Law Number 20 Year 2016 and Government Regulation Number 51 Year 2007 on Geographical Indication have been explained in general the legal protection of Geographical Indication can be given if the subject matter have legal standing. To obtain legal standing can be done by registering Geographical Indication to ensure legal certainty. And the duration of protection may take place indefinitely as long as the characteristics and / or qualities underlying the protection are provided. Indonesia as an archipelagic country is very famous for its natural wealth. Unfortunately, there are still many Geographical Indications of Indonesia that are registered by the Foreign Marks that cause Indonesia to suffer economic losses, therefore it is necessary to take a recovery effort so that Geographical Indication that should be owned by the Indonesian nation can be re-owned by Indonesia.